Laser-Induced Breakdown Spectroscopy analysis of polymers in three different atmospheres - Ivana Chamradová; Pavel Pořízka; Jozef Kaiser (Polymer Testing, 2021)
This paper deals with the analysis of polymer materials of various composition and molecular structure using Laser-Induced Breakdown Spectroscopy (LIBS). To make the discussion more transparent, we studied structurally different polymer samples using LIBS in various atmospheres (air, He, Ar) and examined their influence on signal response. We chose aliphatic (PP, PA 66, POM) and aromatic (PS, ABS) polymers with/without heterogeneous atoms (N, O) in their backbone structure. The emission spectra of all examined polymers are exceedingly similar; they exhibit a characteristic atomic/ionic emission line from four biogenic elements (C, H, N, O) and specific molecular emission bands. We focused on intensities of spectral molecular bands such as carbon dimer (C2 Swan system at 516.5 nm) and cyano (CN band at 338.3 nm) bands as a response to various atmospheres. Sources of molecular bands are native bonds and bonds created from an interaction of plasma with buffers gas molecules. Here, we present a correlation between the polymer structure and signal responses. Finally, Principal Component Analysis was used to further assess the influence of ambient atmospheres on the clustering of LIBS data originating from various polymer samples.